EXERCISE PERFORMANCE, PHYSICAL ACTIVITY, AND HEALTH-RELATED QUALITY OF LIFE IN SUBJECTS WITH STABLE ANGINA - Gardner, Andrew W. (2011)
We compared exercise performance, daily physical activity, and health-related quality of life in 115 subjects with stable angina and 441 controls without coronary artery disease or stable angina. Subjects with stable angina had shorter 6-min walk distance (p = 0.003), and lower total leisure-time physical activity (p = 0.003) than the controls. Group differences in these measures remained (p < 0.05) after adjusting for age, race, current smoking, diabetes, hypertension and obesity. Subjects with stable angina also had lower health-related quality of life for physical function (p < 0.001), general health (p = 0.002) and vitality (p < 0.001), but group differences did not remain (p > 0.05) after adjustment for co-morbid conditions. Subjects with stable angina have impaired exercise performance and reduced daily physical activity. Thus, they are prime candidates for exercise interventions designed to improve daily physical activity and lower extremity strength levels.